Analisis Pelanggaran Etika Profesi pada Kasus Kebocoran Data Aparatur Sipil Negara Tahun 2024 - Rofi Nazar Amrikin (CV. ITTC INDONESIA, 2025)
This study analyzes the ethical violations in the 2024 case of personal data leakage of 4.7 million Indonesian civil servants (ASN). The research aims to identify the factors causing the leakage, examine it through the perspective of professional ethics in information technology, and highlight its ethical, social, and legal impacts. A literature-based qualitative approach was used, drawing on academic journals, media reports, and government documents. Findings show that technical weaknesses, insufficient application of professional ethics, lack of supervision, and weak regulations contributed to the case. Ethical violations identified include lack of professional responsibility, neglect of individual privacy, non-compliance with security standards, and disregard for social consequences. The impacts include declining public trust, heightened risks of cybercrime, and legal vulnerabilities. Recommendations include strengthening data security systems, enforcing regulations, improving ethical awareness, and ensuring transparency in communication.